Numerical modelling of grouted anchors in masonry walls - Pereira, João Miguel (2022)
This work aims to numerically simulate experimental pull-out tests in masonry wall anchors. Advanced Finite Element (FE) 3D models were built to fully reproduce the loadbearing capacity, the failure mode, the stresses and the force-displacement curve and, in general, all the phenomena involved for both brick and stone specimens. Three different modelling approaches were considered. First, a macro-model was adopted, where both brick and stone masonry were assumed as a homogeneous isotropic material. The steel bar and the grouted mortar of the anchor system were considered linear elastic and the system was placed in the specimen using interfaces. The second approach was a unit model, developed with the aim to reproduce the influence of the unit where the anchoring fastening is located. The last approach studied was a micro-model, where both the units and the mortar are considered. The challenge in modelling these systems is highlighted from the different modelling strategies used and compared.